Peta Distribusi Zakat, Infak, Dan Sedekah (Studi Developmental pada BAZNAS Kabupaten Jombang) - Hidayati, Athi'; Chamim, Muhammad; Huda, Sokhi; Haryanti, Peni (UIN Sunan Kudus, 2020)
This study describes the maps and strategies of developing the distribution of zakat, infak, and alms (ZIA) in Jombang regency. To achieve this goal, the study used field qualitative and developmental approaches, and descriptive analysis technique. There are four points of conclusion. Firstly, the zakat mustahik and the distribution target of infak and alms in Jombang are 71,421 pre prosperous families. Secondly, the development of ZIA distribution programs in Jombang Regency covers: (a) creativity of distribution programs, (b) publication and dissemination strategy, (c) print and web-based information, (d) online and offline services, (e) operational picture of ZIA distribution and its control patterns. Thirdly, the development of managerial tools for the distribution of ZIS includes: (1) judicial, institutional, and operational financial instruments, (2) workplace equipment and necessary facilities, (3) offline and online media information devices, (4) HR tools. Fourth, supporting factors: (1) the normative basis of the Qur’an and the Hadith; (2) juridical foundation in the form of zakat law; (3) structural support; (4) operational fund guarantee; (5) organizational management system supported by the availability of building, space, and representative work facilities, and its human resources; (6) cooperation network with agencies, companies, and universities in accordance with the needs of the ZIA distribution development program. Inhibiting factors cover: (1) no development of information media available to facilitate communication of ZIA distribution programs; (2) not yet available part of human resources needed according to requirement of distribution development; (3) not yet optimal management function and organizational management as the main strength of ZIA distribution programs.